Meanings and robustness: Propositions for enhancing benefit sharing in social-ecological systems. Issue 2 (August 2014) - van Wyk, Ernita; Breen, Charles; Freimund, Wayne
Given increased pressure on natural resources to deliver benefits, complex trade-offs and the regulation of behaviours in relation to benefits is of key concern. Behaviours that signify resistance to the rules according to which benefits are allocated prompt us to consider causal links and feedbacks between benefits, perceptions of benefits, meanings attached to the benefits, and the regulatory instruments that mediate the distribution of benefits. An understanding of how meanings influence the perception of benefits exposes the complexity inherent in how people perceive and allocate value to natural resource benefits. Meanings are personal, sometimes overlapping, context dependent and variable across space and time. A challenge in directing resource user behaviour in common pool resources is that the relationship between the resource and resource use is typically not interpreted to include the manner in which users associate resource benefits with meanings. We propose that collective ordering of meanings and associated rules help to direct behaviours and in doing so they contribute to the purposeful maintenance of desirable elements of a social-ecological system (i.e. robustness). Using an example, we illustrate how tensions around benefit sharing are rooted in the emergence and changing prioritisation of contexts and meanings over time. The importance of eliciting, ordering and sanctioning of meanings is emphasised. We conclude by discussing the implications for robustness and benefit sharing in social-ecological systems and we comment on the usefulness and limitations of the framework.